Environmental DNA–RNA dynamics provide insights for effective monitoring of marine invasive species - Michelle Scriver; Ulla vonAmmon; Xavier Pochon; Vanessa Arranz; Jo‐Ann L. Stanton; Neil J. Gemmell; Anastasija Zaiko (Environmental DNA, 2024)
Abstract Environmental DNA and RNA (eDNA/eRNA) can serve as molecular tools for biodiversity monitoring and biosecurity surveillance. However, uncertainties still exist regarding the persistence and dynamics of marine nucleic acids in the environment and the effects of post‐sampling storage on species detectability. To bridge these gaps, an experiment was conducted in an Auckland marina, a known New Zealand entry point for marine non‐indigenous species (NIS). We targeted a prominent invader, the Mediterranean fanworm Sabella spallanzanii, for eDNA/eRNA‐based detection. Permeable dialysis bags filled with seawater collected near an S. spallanzanii colony were deployed in the marina to simulate environmental conditions, with a subset of bags stored on ice to mimic field storage conditions. Sabella spallanzanii eDNA/eRNA signal was quantified using droplet digital PCR on samples collected over 24 h of dialysis bag deployment. Results challenged traditional first‐order decay models, showing inconsistent eDNA/eRNA signal patterns and no significant concentration changes between 0 and 24 h. Consequently, total eDNA fragmentation was assessed using the Agilent 2100 Bioanalyzer® electrophoresis system, which revealed a rise in the number of total eDNA fragments and an unexpected increase in the median fragment size of total eDNA under field conditions over time, likely originating from the ambient microbiome. Additional analysis using long‐read sequencing (Oxford Nanopore Technologies, UK) revealed an increase in microbial eDNA reads within the in‐field samples, suggesting potential microbial growth within the dialysis bags. In contrast, the ice‐stored samples exhibited no significant changes in the number of reads assigned to microbial taxa, implying limited microbial growth in cold storage. These findings provide insights into total eDNA dynamics and its potential impact on targeted eDNA concentration and detection. Further comprehensive research on eDNA/eRNA dynamics, particularly focused on eRNA, is essential, as this understanding is crucial for refining survey interpretation and sampling design for effective environmental management.